Risk Management Analysis Based on ISO 31000:2018 in Culinary MSMEs in Bandung City (Case Study at Warung Olis) - Rizwandi, Hafiz Fazie; Fitriyanto, Muhammad Zaki Aaqila; Heriyandi, Agnelia Septia; Widyaningsih, Aristanti (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2026)
This study aims to analyze the application of risk management at Warung Olis MSMEs in maintaining business sustainability amid operational and market challenges. The research uses a qualitative method with a case study approach through in-depth interviews with Warung Olis owners and direct observation of daily operational activities. Risk analysis is carried out with reference to the ISO 31000:2018 framework, which includes the stages of risk identification, analysis, evaluation, and mitigation. The results of the study identified six main risks, namely the risk of raw material shortages (R1), social environmental risk (R2), risk of negligence in payment transactions (R3), risk of order serving errors (R4), risk of errors in cash recording and calculation (R5), and market risk due to fluctuations in the number of customers (R6). The analysis results show that market risk is the risk with the highest impact on revenue decline, especially when the number of customers decreases. In addition, cash recording errors and transaction negligence have the potential to disrupt daily financial stability. The main mitigations implemented are the use of digital financial recording applications, recording transactions directly at the time of ordering, as well as menu innovations and social media promotions to maintain sales stability. These efforts are effective in reducing potential losses and improving business financial management in a more structured manner.